Effectiveness of Online Videos to Modify Students' Knowledge and Perceived Barriers Regarding Study Abroad Opportunties - Wilmara Corréa Harder; Thomas H. Bruening (Journal of International Agricultural and Extension Education, 2011)
The need to increase the number of students participating in study abroad is a goal that higher education must recognize. For ten years, the level of participation among students enrolled in colleges of agricultural sciences has remained at constant level. In a society that is globally interconnected, it is imperative that future graduates comprehend various dimensions of culture, agricultural production, and economy to succeed. The purpose of this study was to determine the effectiveness of online videos to modify students’ knowledge and perceived barriers regarding study abroad opportunities. The objectives of this paper are: 1. Describe the amount of learning obtained through watching study abroad videos; 2. Determine changes to students’ perceived barriers regarding their possible participation in study abroad programs. In order to assess students’ perceptions, three online videos were developed. Videos were based on a semester-long study abroad program in Russia and two study tour programs in Puerto Rico and Brazil, respectively. A quasi-experimental research design was used in this study. One hundred fifty six students from nine sections of the first year seminar participated in the study. In this study, the use of online videos was effective in communicating information and diminishing the perceived barriers to study abroad. Other colleges and programs could use this strategy to promote their international programs. In addition, administrators could use the results of this study to develop online videos to teach content and dispel myths regarding study abroad programs.
Keywords: Study abroad; agriculture; online videos; learning; barriers; media; and teaching